Accounting in the fourth industrial revolution: Exploration of digital currency exchanges using AHP method - Sadeghi, Samaneh; Barzegari, Jamal (goodwood publishing, 2020)
Purpose: The present study aimed to analyze and select the best exchange in the field of digital currencies with a futuristic perspective. Research methodology: The research method in this article is to use Analytic Hierarchy Process (AHP) to identify the strengths and weaknesses of each of these exchanges and analyze their coefficients according to the criteria of security, support, commission, number of currency codes, authentication, and trading volume. Results: The most important criteria in choosing the best digital currency exchange are: security, support, commission, number of currency codes, authentication and trading volume. Limitations: The limitations of this research can be the characteristics of digital exchanges in the field of providing digital currency cryptographic services in accordance with the framework of the Fourth Industrial Revolution. Contribution: According to the weight of the obtained criteria will be prioritized, which from the results and analysis obtained in this research can be used to invest in the field of currency cryptography and select the top exchange.